Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

A Framework for Measurable Value Propositions of Mobile Applications - N., N.

Model-Based Product Configuration in Augmented Reality Applications - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Alltagssituation in der Kita: Ramadan feiern in der Kita - Kamcili-Yildiz, Naciye (Religionspädagogik für Erzieherinnen. Ein ökumenisches Arbeitsbuch)

Interreligiöse Kooperation im Religionsunterricht: Perspektiven und Zwischenfazit zum Lernen in heterogenen Lerngruppen - Kamcili-Yildiz, Naciye; Woppowa, Jan; Caruso, Carina; Konsek, Lukas (Religion in der Schule. Pädagogische Praxis zwischen Diskriminierung und Anerkennung)

,Dann mache ich einfach mal weiter.‘ – Zur Lehrsteuerung der Studierenden in die Indifferenz - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Mindsets religiöser Pluralität als Faktor in der (islamischen) Religionslehrer*innenbildung - Kamcili-Yildiz, Naciye; Mauritz, Gerrit; Reis, Oliver; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Pluralisation of Theologies at European Universities

Säkular und religiös: Herausforderungen für Christentum und Islam

Lesen lernen von Aufgabentexten - Dröse, Jennifer; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Physik in der Lehrerinnen- und Lehrerbildung. Auf dem Weg zu empirisch fundierten Curricula - Reinhold, Peter; Riese, Josef (Handbuch Lehrerinnen- und Lehrerbildung)

Die Messung der Fähigkeit zur Unterrichtsplanung im Fach Physik mit Hilfe eines standardisierten Performanztests - Schröder, Jan; Riese, Josef; Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Die Unterrichtsplanung stellt eine zentrale berufliche Anforderung an (Physik‑)Lehrkräfte dar. Bereits im Lehramtsstudium sollen grundlegende Fähigkeiten zur Unterrichtsplanung erworben und im Rahmen von schulpraktischen Phasen erprobt bzw. erweitert werden. Unklar ist jedoch, inwieweit das professionelle Wissen, das Lehramtsstudierende in ihren fachlichen, fachdidaktischen und erziehungswissenschaftlichen Studienteilen erwerben, tatsächlich bei der Planung von Fachunterricht genutzt wird. Ebenso gibt es nur punktuelle Erkenntnisse über die Entwicklung der Fähigkeit zur Unterrichtsplanung im Lehramtsstudium. Um diese Fragen zu klären, sind Messverfahren erforderlich, die die Fähigkeiten zur Unterrichtsplanung valide erfassen können und die gleichzeitig ökonomisch auswertbar sind, um Fallzahlen realisieren zu können, die auch kleine Effekte auflösen. Bisherige Ansätze, die reale Handlungsproben der Unterrichtsplanung (z. B. schriftliche Unterrichtsentwürfe) untersuchen, stehen vor der methodischen Herausforderung, dass die Generierung eines Fähigkeitsmaßes höchst anspruchsvoll ist, da reale Planungen individuell sehr unterschiedlich angelegt sind und vielen Randbedingungen unterliegen, die statistisch kaum kontrollierbar sind. In diesem Beitrag wird daher ein sogenannter Performanztest zur Erfassung der Fähigkeit zur Unterrichtsplanung vorgestellt und diskutiert. Ein Performanztest ist ein Verfahren, in dem in einem realitätsnahen Setting Handlungen unter standardisierten Rahmenbedingungen simuliert werden. Neben der theoriegeleiteten Entwicklung des Instruments und Vorstudien zur Sammlung von Validitätsargumenten werden auch erste Ergebnisse dargestellt, die aus Erhebungen vor und nach einem Praxissemester an vier Universitäten in drei Bundesländern resultieren ( N = 174 Unterrichtsplanungen). Dabei stellt sich das Testverfahren als ausreichend sensitiv heraus, um für N = 68 Testpersonen (ca. 20 % Dropout) erwartungstreu eine signifikante Zunahme des Testscores während des Praxissemesters, welches als Lerngelegenheit angenommen werden kann, zu messen.

Development of Prospective Physics Teachers’ Professional Knowledge and Skills during a One-Semester School Internship - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Schecker, Horst; Schröder, Jan (Student Learning in German Higher Education)

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik, 19)

The Story of Mary as a Feminine Counterpart to the Story of Joseph - Haghani Fazl, Mohammad (Religious Inquiries, 9)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Strain parameters at hot rolling of aluminum strips reinforced with steel netting - Stolbchenko, Mykhailo; Makeieva, Hanna; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Journal of Sandwich Structures & Materials)
This experiment studied the strain parameters of rolling an aluminum matrix when wire netting is inserted between aluminum layers. During the experiment, two types of stainless steel fabric netting oriented parallel and diagonal to the rolling axis were placed between two aluminum strips and rolled. Multiple rolling processes were performed in which the temperature and pressure on the material were varied to produce bonding of matrix layers. During the study, the following main investigations were made: strain on areas of longitudinal and transverse cross sections of the composite was measured; stretching and ovalization of net wiring and changes in the net cell angles were determined; mechanical properties of composites along the rolling direction were tested. The main contradiction resulting from this experiment was as follows: the contact pressure required for the bonding of aluminum layers produces extreme tensile strain on the inserted net wires, reducing the mechanical properties of the reinforcing net and thus reducing properties of the entire composite. Optimal results in the longitudinal tension tests were achieved by using strips with diagonally oriented net-reinforcement.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The mechanical properties of rolled wire-reinforced aluminum composites at different strain values - Stolbchenko, Mykhailo; Frolov, Yaroslav; Makeieva, Hanna; Grydin, Olexandr; Tershakovec, Michael A.; Schaper, Mirko (Mechanics of Advanced Materials and Structures)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christopher; Liß, Jan; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, W.; Hagen, L.; Schaak, C.; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, M. E.; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, Tobias; Teng, Zhenjie; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Influence of Microstructure in Near‐Surface Areas of Feedstocks on the Bond Strength of Roll Bonded Aluminum Clads - Grydin, Olexandr; Matzelt, Manuel; Andreiev, Anatolii; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslaw; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Dialektatlas Mittleres Westdeutschland (DMW) - Methodik, Akquise, Exploration und Analyse - Wallmeier, Nadine; Kuhmichel, Katrin; Gehrke, Gero; Sauermilch, Stephanie (Niederdeutsches Wort)

Messung der Fähigkeit zur Unterrichtsplanung bei Lehramtsstudierenden - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Ursachen für Veränderungen des physikdidaktischen Wissens im Studium - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Basismodelle in Unterrichtsplanungen im Praxissemester Physik - Buschhütter, David; Mutschler, Tanja; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Wie entwickeln sich Wissen und Fähigkeiten im Physiklehramtsstudium? - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Estimation of acoustic wave non-linearity in ultrasonic measurement systems - Claes, Leander; Steidl, Carolin; Hetkämper, Tim; Henning, Bernd (arXiv.org)

Does Informational Equivalence Preserve Strategic Behavior? Experimental Results on Trockel’s Model of Selten’s Chain Store Story - Duman, Papatya (Games)
The purpose of this study is to experimentally test Trockel’s game, which is a modelling of the classical Chain Store Game (CSG), and determine whether one of the two theories of Equality and Deterrence may better account for the observed behavior. The CSG is an example of a simple game in extensive form where the actual behavior of well-informed players cannot be expected to agree with the clear results of game theoretical reasoning. To explain the disagreement between the theory and the expected behavior, Trockel’s game is proposed as an alternative modelling of the scenario. The existence of more than one equilibrium in Trockel’s game opens a door for reputation building. This study is the first attempt to experimentally test this alternative game with the same purpose. According to my data, there is some evidence in favor of both Equality and Deterrence Hypotheses. However, since the strategies compatible with the Equality Hypothesis are played more frequently, I observe some patterns which share the same intuition with the Deterrence Hypothesis.
Keywords: Applied Mathematics; Statistics; Probability and Uncertainty; Statistics and Probability

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Frühe alltagsintegrierte mathematische Bildung. Eine Einleitung - Bruns, Julia; Vogtländer, A. (Frühe alltagsintegrierte mathematische Bildung. Handreichung für Lehrende)

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Interaktionen in mathematischen Spielsituationen in Kindertagesstätte und Familie - Meyer, Lena; Tabeling, Laura; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Adaptionshandlungen von Multiplikatorinnen und Multiplikatoren zur frühen mathematischen Bildung – Beschreibung und Bewertung aus fachbezogener Perspektive - Bruns, Julia; Schopferer, Theresa; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Die Implementation früher mathematischer Bildung in Kindertagesstätten kann durch fachdidaktische Fortbildungen für frühpädagogische Fachkräfte unterstützt werden. Um Fachkräfte in der Breite zu erreichen, erscheint ein scaling up Ansatz geeignet, bei dem aufbauend auf das Fortbildungskonzept EmMa – Erzieherinnen und Erzieher machen Mathematik Multiplikatorinnen und Multiplikatoren qualifiziert werden. Dabei ergibt sich die Herausforderung, dass Fortbildende im Elementarbereich kaum mathematisches und mathematikdidaktisches Wissen mitbringen. Der Kontext dieser Studie ist der scaling up Prozess der Fortbildung EmMa unter diesen Umständen. Das Erkenntnisinteresse liegt in der Beschreibung und Bewertung der Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren. Für die Bewertung der Adaptionen werden zwei Kriterien herangezogen: (1) das Kriterium der Präzision, das die Vollständigkeit und Klarheit der Inhalte umfasst und (2) das Kriterium der fachlichen Korrektheit, das durch das Ausbleiben fachbezogener Fehler beschrieben wird. Analysiert werden dabei die theoretischen, fachbezogenen Phasen der von Multiplikatorinnen und Multiplikatoren durchgeführten Fortbildung zur frühen mathematischen Bildung, da davon ausgegangen wird, dass insbesondere diese theoretischen Inhalte für diese Gruppe von Multiplikatorinnen und Multiplikatoren eine Herausforderung darstellen. Zur Untersuchung wurde eine videogestützte, qualitative Feldstudie mit N = 8 Fällen durchgeführt. Mit Hilfe der qualitativen Inhaltsanalyse wurden die Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren charakterisiert und hinsichtlich ihrer Präzision und der fachlichen Fehler in diesen Adaptionen analysiert. Dabei zeigte sich, dass der eigenständige Umgang mit den mathematischen und mathematikdidaktischen Inhalten des Fortbildungskonzepts EmMa trotz intensiver Unterstützung anspruchsvoll und bei vielen Multiplikatorinnen und Multiplikatoren mit fachbezogenen Fehlern verbunden ist. Implikationen dieser Ergebnisse für die weitere Forschung werden diskutiert.

Situational Perception in Mathematics (SPiM)—Results of a Cross-Country Study in Austria and Norway - Bruns, Julia; Carlsen, Martin; Eichen, Lars; Erfjord, Ingvald; Hundeland, Per Sigurd (Mathematics Education in the Early Years)

Mathematisches Fachwissen von frühpädagogischen Fachpersonen im Spannungsfeld zwischen Disziplin- und Praxis - Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

“Why don’t you make a drawing?" Motivation and strategy use in mathematical modelling - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Rellensmann, J. (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education: PME)

Measuring and investigating strategic knowledge about drawing to solve geometry modelling problems - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (ZDM – Mathematics Education)

Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita – Grundschule. Herausgegeben von: Höke, Julia; Büker, Petra, Ogrodowski, Jana & Vollmann, Britta. Unter Mitarbeit von Alina Bruyn und Theresa Driller. Dieses Instrument liegt seit 2021 ebenfalls in vollständiger englischer Übersetzung vor: https://blogs.uni-paderborn.de/pq3-international/ - Herding, Jana

Zur Bedeutung von Integrationserfahrungen in der Grundschulzeit aus der Retroperspektive junger Erwachsener: eine Interviewstudie - Herding, Jana; Ogrodowski, J. (Diversität und soziale Ungleichheit. Herausforderungen an die Integrationsleistung der Grundschule. Jahrbuch Grundschulforschung)

Digitale Transformationsprozesse in der beruflichen Benachteiligtenförderung – erste Ergebnisse einer qualitativen Studie - Schemmer, Susanne Jutta (Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf - Schemmer, Susanne Jutta; Heisler, Dietmar (bwp@Berufs-und Wirtschaftspädagogik – online, (24.06.2020))

Semantic-based End-to-End Learning for Typhoon Intensity Prediction - Zahera, H.M.A (Arxiv)

ProBERT: Product Data Classification with Fine-tuning BERT Model. - Zahera, H.M.A; Sherif, Mohamed (MWPD@ ISWC)

On the multi-domain compact finite difference relaxation method for high dimensional chaos: The nine-dimensional Lorenz system - Kouagou, N.J.; Dlamini, P.G.; Simelane, S.M. (Alexandria Engineering Journal)
In this paper, we implement the multidomain compact finite difference method to numerically study high dimensional chaos by considering the nine-dimensional Lorenz system. Most of the existing numerical methods converge slowly for this kind of problems and this results in inaccurate approximations. Though highly accurate, the compact finite difference method becomes less accurate for problems characterized by chaotic solutions, even with an increase in the number of grid points. As a result, in this work, we adopt the multidomain approach. This approach remarkably improves the results as well as the efficiency of the method.
Keywords: Multidomain; Compact finite difference; 9D Lorenz system

Geschlechterverwirrungen. Was wir wissen, was wir glauben und was nicht stimmt
In Geschlechterfragen kann jede*r mitreden – und ist dabei oft von Irrtümern und Vorurteilen geleitet. 32 Autorinnen und Autoren befassen sich in diesem Band mit unserem Wissen, Glauben und Nichtwissen zu Geschlecht und »Gender«. Die Beiträge, die von historischen über philosophische und körperbezogene bis zu politischen Themen reichen, wollen sachkundig informieren, seriös aufklären – und auch ein wenig verwirren, indem sie ihren Gegenstand von unterschiedlichen Seiten betrachten und dabei zeigen, was wir nicht wissen.

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

DeepWind: An Accurate Wind Turbine Condition Monitoring Framework via Deep Learning on Embedded Platforms - Ghasemzadeh Mohammadi, Hassan; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Kuschel, Maurice; Jentzsch, Felix Paul; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Design and Implementation of a ReconOS-based TensorFlow Lite Delegate Architecture - Jentzsch, Felix P.
Modern machine learning (ML) techniques continue to move into the embedded system space because traditional centralized compute resources do not suit certain application domains, for example in mobile or real-time environments. Google’s TensorFlow Lite (TFLite) framework supports this shift from cloud to edge computing and makes ML inference accessible on resource-constrained devices. While it offers the possibility to partially delegate computation to hardware accelerators, there is no such “delegate” available to utilize the promising characteristics of reconfigurable hardware. This thesis incorporates modern platform FPGAs into TFLite by implementing a modular delegate framework, which allows accelerators within the programmable logic to take over the execution of neural network layers. To facilitate the necessary hardware/software codesign, the FPGA delegate is based on the operating system for reconfigurable computing (ReconOS), whose partial reconfiguration support enables the instantiation of model-tailored accelerator architectures. In the hardware back-end, a streaming-based prototype accelerator for the MobileNet model family showcases the working order of the platform, but falls short of the desired performance. Thus, it indicates the need for further exploration of alternative accelerator designs, which the delegate could automatically synthesize to meet a model’s demands.

Global generalized solutions to a forager–exploiter model with superlinear degradation and their eventual regularity properties - Black, Tobias (Mathematical Models and Methods in Applied Sciences)
Keywords: Applied Mathematics; Modeling and Simulation

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

An Algorithmic Solution for Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef (the International Journal On Advances in Software)

Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)

Von Interkultureller Kompetenz und sportpädagogischem Können in postmigrantischen Gesellschaften. Grundlagen und Weiterentwicklung eines Forschungsprogramms - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Möhwald, Aiko Julia (Sport im Kontext globaler Zusammenarbeit)

Sportdidaktik - Grimminger-Seidensticker, Elke; Oesterhelt, V.; Gerlach, E.; Friedrich, G. (Lernen im Fach und über das Fach hinaus)

Zum Umgang mit Heterogenität im Sportunterricht - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports)

Machthandlungen von Schüler*innen im Sportunterricht – Welche Rolle spielt das Sportlehrer*innenhandeln? - Grimminger-Seidensticker, Elke (sportunterricht)

Körperbild, Bewegung und Sport in der Wahrnehmung von Grundschulkindern. Ergebnisse einer explorativen lnterviewstudie - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia (sportunterricht)

A 14-weeks intervention study on changing preservice teachers’ psychological perspectives related to teaching inclusively: Explicit and implicit attitude, self-efficacy, and stress perception towards inclusion - Grimminger-Seidensticker, Elke; Lautenbach, F.; Heyder, A.; Korte, J.; Möhwald, Aiko Julia (Frontiers in Education)

Quantitative and qualitative results of a body image pilot intervention in (pre)adolescent girls - Grimminger-Seidensticker, Elke; Korte, J. (Journal of Physical Education & Health)

Health concepts among socially disadvantaged children in France, Germany and Switzerland - Grimminger-Seidensticker, Elke; Aceti, Monica; Knobé, Sandrine; Vieille Marchiset, Gilles (Health Promotion International)
Summary As health concepts develop through exposure to, and experience with particular contexts, and as health concepts influence health behaviour, it is important for actors in health promotion programmes to understand an individual’s health concepts. This study focussed on health concepts among socially disadvantaged children in France, Germany, Italy and Switzerland—a hitherto less researched population group. We conducted focus groups with a total of 167 children aged 7–11 years (mean=8.76 years, SD=0.68). The aim of this study was to explore if the life situation across four different countries leads to similar health concepts, and how the particular, national health discourses are reflected in the children’s health concepts. The data were analysed through a structured qualitative content analysis and revealed four categories: ‘Symbols/symptoms of health/illness’, ‘Emotionality’, ‘Healthy/unhealthy practices’, and ‘Consequences of health problems’. The children’s health concepts are linked to concrete events and objects, and they are able to think in logical sequences. However, the children’s causal argumentation is uni-dimensional; they do not cover the complexity of the development of health problems. In particular, overweight stands for illness and is exclusively the result of unhealthy practices. In their concepts, the children reflect the national health promotion programme discourses about overweight. They seem to understand the messages of health education as ‘behaving well means being healthy’; however, such a health education message initiates accusations of ‘unhealthy persons’. In consequence, challenges for sensitive health education programmes (at school) are discussed.

A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education)

SUBCLINICAL DISORDERED EATING AND BODY DISSATISFACTION IN NORMAL WEIGHT CHILDREN—THE ROLE OF PHYSICAL ACTIVITY AND MOTIVES TO EXERCISE - Grimminger-Seidensticker, Elke; Korte, Johanna; Möhwald, Aiko; Trojan, Jörg (Journal of Physical Education & Health)

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan
Review von Holger Zellentin, Review of Qur'anic Research, Vol. 7 no. 5 (2021) Rezension von Bertram Schmitz, Theologische Literaturzeitung, Nr. 7, 2021, Spalte 657-658 Review von Sebastian Bitsch, Der Islam, Band 98, Heft 2, 2021, 591-598

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2011.06434)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold.

Körperspannung trainieren : auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)TurnenKörperspannung trainieren: auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)Turnen - Dörrer, Hans-Joachim; Köster, Carolin (Sportpädagogik)

Language Teachers and Crowdsourcing - Arhar Holdt, Špela; Zanasi, Lorenzo; Weber, Tassja; Volodina, Elena; Rodosthenous, Christos; Ordulj, Antonia; Miloshevska, Lina; Lazić Konjik, Ivana; Koeva, Svetla; Kasperavičienė, Ramunė; Hatipoglu, Ciler; Fort, Karën; et al. (Rasprave Instituta za hrvatski jezik i jezikoslovlje)
The paper presents a cross-European survey on teachers and crowdsourcing. The survey examines how familiar language teachers are with the concept of crowdsourcing and addresses their attitude towards including crowdsourcing into language teaching activities. The survey was administrated via an online questionnaire and collected volunteers’ data on: (a) teachers’ experience with organizing crowdsourcing activities for students/pupils, (b) the development of crowdsourced resources and materials as well as (c) teachers’ motivation for participating in or employing crowdsourcing activities. The questionnaire was disseminated in over 30 European countries. The final sample comprises 1129 language teachers aged 20 to 65, mostly working at institutions of tertiary education. The data indicates that many participants are not familiar with the concept of crowdsourcing resulting in a low rate of crowdsourcing activities in the classroom. However, a high percentage of responding teachers is potentially willing to crowdsource teaching materials for the language(s) they teach. They are particularly willing to collaborate with other teachers in the creation of interactive digital learning materials, and to select, edit, and share language examples for exercises or tests. Since the inclusion of crowdsourcing activities in language teaching is still in its initial stage, steps for further research are highlighted.
Keywords: Linguistics and Language; Language and Linguistics

Präpositionen und Deutsch als Fremdsprache: Quantitative Fallstudien im Lernerkorpus MERLIN - Weber, Tassja
Die Dissertation beschäftigt sich mit dem Gebrauch von Präpositionen (z. B. an, für) und Präpositionalphrasen (z. B. an der Wand, für dich) durch Lernende des Deutschen als Fremdsprache (DaF). Es wird untersucht, welche ausgewählten Variablen den Gebrauch dieser Strukturen beeinflussen. Der Schwerpunkt liegt dabei auf Gebrauchsschwierigkeiten. Auf Basis lernersprachlicher Daten im digitalen, frei verfügbaren Lernerkorpus MERLIN (merlin-platform.eu) und unter Berücksichtigung grundlegender Annahmen aktueller Spracherwerbstheorien werden quantitativ ausgerichtete Fallstudien zu folgenden Einflussvariablen durchgeführt: Die Erstsprache der Lernenden, die Sprachkompetenz, die syntaktische Funktion der PP und der semantische Gehalt der Präposition. Die Arbeit bettet sich ein in die Lernerkorpusforschung an der Schnittstelle zur Zweit- und Fremdspracherwerbsforschung. Die Ergebnisse zeigen insgesamt für alle Einflussvariablen einen Effekt und bestätigen damit den Einfluss intralingualer sowie interlingualer Merkmale im Sprachgebrauch von Lernenden. Dabei wird deutlich, dass die Gebrauchsschwierigkeiten nicht quantitativer (Korrektheit), sondern eher qualitativer Natur (Fehlertypen) sind. Die Dissertation liefert empirisch fundierte Erkenntnisse zu Schwierigkeiten im Gebrauch von Präpositionen und PP durch DaF-Lernende, für die bisher systematische, korpusgestützte Untersuchungen fehlten. Die Arbeit zeigt dabei exemplarisch auf, wie Annahmen aus der Spracherwerbsforschung anhand von Lernerkorpusdaten überprüft und mögliche Einflussvariablen im Sprachgebrauch ermittelt werden können. Die Erkenntnisse sind auch für andere Forschungsfelder (u.a. Fremdsprachenunterricht und maschinelle Sprachverarbeitung) relevant.
Keywords: Deutsch als Fremdsprache; Korpuslinguistik; Lernerkorpora; Präpositionen; Präpositionalphrasen; Grammatik; Regressionsanalyse

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Janus-type dual emission of a Cyclometalated Iron(III) complex - Bauer, Matthias; Steube, Jakob; Päpcke, Ayla; Bokareva, Olga; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan
Photoactive compounds are essential for photocatalytic and luminescent applications, such as photoredox catalysis or light emitting diodes. However, the substitution of noble metals, which are almost exclusively used, by base metals remains a major challenge on the way to a more sustainable world.1 Iron is a dream candidate for this ambitious aim.2 But compared to noble metal complexes that show long-lived metal-to-ligand charge-transfer (MLCT) states, realization of emissive and photoactive iron complexes is demanding, due to the fast deactivation of charge transfer states into non-emissive inactive states. No MLCT emission has been observed for monometallic iron complexes before. Consequently, dual emission could also not yet be realized with iron complexes, as it is a very rare property even of noble metal compounds. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1’-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing Janus-type dual emission by combining LMCT (ligand-to-metal charge transfer) with MLCT luminescence. The respective excited states are characterized by a record lifetime of τ MLCT = 4.2 ns, and a moderate τ LMCT = 0.2 ns. Only two emissive Fe III compounds are known so far and they show LMCT luminescence only.3,4 The unique properties of the presented complex are caused by the specific ligand design combining four N-heterocyclic carbenes with two cyclometalating groups, using the σ-donor strength of six carbon atoms and the acceptor capabilities of the central phenyl rings. Spectroscopically, doublet manifolds could be identified in the deactivation process, while (TD)DFT analysis revealed the presence of quartets as well. With three key advancements of realizing the first iron complex showing dual luminescence, a MLCT luminescence and a world record MLCT lifetime, the results constitute a basis for future application of iron complexes as white light emitters and new photocatalytic reactions making use of the Janus-type properties of the developed complex.

Benchmarking the Lifecycle of Knowledge Graphs - Röder, Michael; Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)
Keywords: dice group_aksw roeder sherif saleem fconrads ngonga

Applying edge-counting semantic similarities to Link Discovery: Scalability and Accuracy - Georgala, Kleanthi; Röder, Michael; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
With the growth in number and variety of RDF datasets comes an in- creasing need for both scalable and accurate solutions to support link discovery at instance level within and across these datasets. In contrast to ontology matching, most linking frameworks rely solely on string similarities to this end. The limited use of semantic similarities when linking instances is partly due to the current literature stating that they (1) do not improve the F-measure of instance linking approaches and (2) are impractical to use because they lack time efficiency. We revisit the combination of string and semantic similarities for linking instances. Contrary to the literature, our results suggest that this combination can improve the F-measure achieved by instance linking systems when the combination of the measures is performed by a machine learning approach. To achieve this in- sight, we had to address the scalability of semantic similarities. We hence present a framework for the rapid computation of semantic similarities based on edge counting. This runtime improvement allowed us to run an evaluation of 5 bench- mark datasets. Our results suggest that combining string and semantic similarities can improve the F-measure by up to 6% absolute.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal roeder georgala

LIGON – Link Discovery with Noisy Oracles - Sherif, Mohamed; Dreßler}, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Link discovery plays a key role in the integration and use of data across RDF knowledge graphs. Active learning approaches are a common family of solutions to address the problem of learning how to compute links from users. So far, only active learning from perfect oracles has been considered in the literature. However, real oracles are often far from perfect (e.g., in crowdsourcing). We hence study the problem of learning how to compute links across knowledge graphs from noisy oracles, i.e., oracles that are not guaranteed to return correct classification results. We present a novel approach for link discovery based on a probabilistic model, with which we estimate the joint odds of the oracles’ guesses. We combine this approach with an iterative learning approach based on refinements. The resulting method, Ligon, is evaluated on 10 benchmark datasets. Our results suggest that Ligon configured with 10 iterations and 10 training examples per iteration achieves more than 95% of the F-measure achieved by state-of-the-art algorithms trained with a perfect oracle. Moreover, Ligon outperforms batch learning approaches devised to be trained with small amounts of training data by more than 40% F-measure on average.
Keywords: 2020 dice simba sherif ligon ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal kevin